Study of Neutrosophic Magnified Translation on Incline Algebra - Surya Manokaran; Muralikrishna Prakasam (Journal of the Indonesian Mathematical Society, 2023)
The concept of magnified translation is studied in Neutrosophic set which is a segregation of mf (membership function) is known as t(truth)mf, i(indeterminate)mf, and f(falsity)mf which has been applied in incline algebra sub - structures and raises with a name called neutrosophic incline substructures are interlinked with the new frame of (nmt) neutrosophic magnified translation. Further, some more engrossing outputs such as homomorphic image, preimage and cartesian product on this neutrosophic magnified translation of incline substructure are investigated.